Feminist Voice in Rajan Mukarung's Hātā Jāne Aghillo Rāta - Mishra, Indira Acharya (Dristikon: A Multidisciplinary Journal, 2019)
Some of the poems in Rajan Mukarung's latest anthology Hātā Jāne Aghillo Rāta [The Night before the Market Day] (2019) are written from the feminist perspective. However, the feminist voice raised in these poems is different from the feminist voice of the main stream Nepali feminist literature which raises the issues of urban, middle class, educated upper caste women from the hills (bourgeoisies women), who aspire liberation from the restrictive traditional gender roles. Unlike the main stream Nepali feminist literature, in these poems, he dramatizes the issues of women from the margin. These are poor and illiterate women from Dalit and ethnic communities who bear the brunt of not only gender discrimination, but also suffer from class and caste discriminations. The article aims to analyze three of the poems from the anthology from the Multicultural feminist perspectives. The finding of the article suggests that these poems raise the voice of marginalized women and demand justice to lower caste and ethnic women whose mores are different from the bourgeoisies' women.